Messenger RNA Vaccine Effectiveness Against Coronavirus Disease 2019 Among Symptomatic Outpatients Aged ≥16 Years in the United States, February–May 2021. (8th September 2021) - Kim, Sara S; Chung, Jessie R; Belongia, Edward A; McLean, Huong Q; King, Jennifer P; Nowalk, Mary Patricia; Zimmerman, Richard K; Balasubramani, Goundappa K; Martin, Emily T; Monto, Arnold S; Lamerato, Lois E; Gaglani, Manjusha; et al.
Abstract: Evaluations of vaccine effectiveness (VE) are important to monitor as coronavirus disease 2019 (COVID-19) vaccines are introduced in the general population. Research staff enrolled symptomatic participants seeking outpatient medical care for COVID-19–like illness or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing from a multisite network. VE was evaluated using the test-negative design. Among 236 SARS-CoV-2 nucleic acid amplification test-positive and 576 test-negative participants aged ≥16 years, the VE of messenger RNA vaccines against COVID-19 was 91% (95% confidence interval, 83%–95%) for full vaccination and 75% (55%–87%) for partial vaccination. Vaccination was associated with prevention of most COVID-19 cases among people seeking outpatient medical care. Abstract : With the test-negative design used to evaluate protection from messenger RNA vaccines, vaccine effectiveness against coronavirus disease 2019 among outpatients aged ≥16 years was 91% (95% confidence interval, 83%–95%) for full vaccination and 75% (55%–87%) for partial vaccination.